The consideration of virial corrections in the diffusion equations. Issue 1 (9th March 2015) - Levin, D; Trutnev, E
Abstract: The diffusion phenomenon is known to be a universal physical process and the basis of many industrial technologies for advanced materials. Abnormalities of diffusion have been observed which cannot be described by existing theory. The diffusion of atoms of the introduction (boron) possessing great energy of dissolution, results in significant deformation of the crystal lattice of iron in the radius of the first coordination spheres. Mayer's approach to the solution of the problem of getting diffusion equation with viral corrections, indicating the account of interparticle interaction in thise systems, has been offered in this work. In the ongoing project the model of diffusion of boron impurities, strongly interacting with the lattice has been described. Further directions in the solution of this problem have been suggested. To explain the anomalies observed in the diffusion mechanism of implementation a comparison of theoretical calculations has been attempted, in particular, in the system iron-boron.